1952
DOI: 10.1111/j.2517-6161.1952.tb00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Rational Decisions

Abstract: Summary This paper deals first with the relationship between the theory of probability and the theory of rational behaviour. A method is then suggested for encouraging people to make accurate probability estimates, a connection with the theory of imformation being mentioned. Finally Wald's theory of statistical decision functions is summarised and generalised and its relation to the theory of rational behaviour is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
450
0
4

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 799 publications
(456 citation statements)
references
References 0 publications
2
450
0
4
Order By: Relevance
“…It was rejected by Keynes, Kyburg, Smith (1961), Good (1951Good ( , 1961 maybe, Ellsberg (1961Ellsberg ( , 2002, I.Levi, T.Seidenfeld, P.Walley among others. I replace confirmational uniqueness by the following requirement:…”
Section: Confirmational Consistency: K Is Consistent If and Only If Cmentioning
confidence: 96%
“…It was rejected by Keynes, Kyburg, Smith (1961), Good (1951Good ( , 1961 maybe, Ellsberg (1961Ellsberg ( , 2002, I.Levi, T.Seidenfeld, P.Walley among others. I replace confirmational uniqueness by the following requirement:…”
Section: Confirmational Consistency: K Is Consistent If and Only If Cmentioning
confidence: 96%
“…For the reconciliation of these additional tertiary readings will be needed, and so on: we have an infinite regress. Good (1952Good ( , 1971) has suggested that the higher one goes in this regress, the less important the values become. It remains to be shown under what psychological circumstances the process coverges so as to assure a unique ultimate reconciliation.…”
Section: Methods Of Reconciliationmentioning
confidence: 99%
“…This gap in the theory and practice of decision analysis and personalist inference was noted as early as the 50's (Good, 1952;Savage, 1954). Good in particular has made significant contributions to various aspects of the problem (Good, 1967(Good, , 1971(Good, , 1976.…”
Section: Introductionmentioning
confidence: 99%
“…The logarithmic scoring rule was proposed by Good [5]; it is strictly proper and has been widely used under various names, including the predictive deviance and the ignorance score.…”
Section: Logarithmic Scorementioning
confidence: 99%